Effects of Industrial Wastewater on the Yield and Trace Element Contents of Red amaranth (Journal of Environmental Science and Natural Resources, 2017)
Assessment the effect of industrial wastewater on the yield and trace element contents of red amaranth was carried out by this study. Thirty wastewater samples were collected from five major environment-polluting industries namely pharmaceuticals, dyeing, leather, food, and plastic industries at three different locations. Atomic Absorption Spectrophotometer was used for analyzing the trace elements in the wastewater-irrigated samples of red amaranth. Higher mean concentrations of Pb, Cd, Ni, Cr, As, Zn, and Cu in red amaranth were 0.97, 0.20, 1.23, 52.72, 0.52, 0.85, and 2.62 ?g g-1. The percentage of yield reduction in red amaranth were 11.06, 12.73, 14.07, 3.46, 7.82 % for T2, T3, T4, T5 and T6 respectively compared to distilled water control (T1). The results concludes that the wastewater samples of pharmaceuticals, dyeing, leather and plastic industries were more polluted than the wastewater of food industries. Vegetables grown in industrial areas contain trace elements viz. Cr, Ni and Cu which would be health hazardous for consumer.J. Environ. Sci. & Natural Resources, 9(2): 27-30 2016